What happens when employers are free to discriminate? Evidence from the English barclays premier fantasy football league - Bryson, Alex; Chevalier, Arnaud (London, 2014)
"Research on employers’ hiring discrimination is limited by the unlawfulness of such activity. Consequently, researchers have focused on the intention to hire. Instead, we rely on a virtual labour market, the Fantasy Football Premier League, where employers can freely exercise their taste for racial discrimination in terms of hiring and firing. The setting allows us to eliminate co-worker, consumer-based and statistical discrimination as potential sources of discrimination, thus isolating the effects of taste-based discrimination. We find no evidence of racial discrimination, either in initial hiring or through the season, in a context where employers are fully aware of current and prospective workers’ productivity."